Research and application of multi-beam antenna technology for home network based on SSPP technology - Shengbing SHI; Jinjin SHAO; Cao SHI (物联网学报)
High-quality home wireless network with large bandwidth, wide coverage, low latency and anti-interference is the key indicator to ensure user experience of fiber to the room (FTTR) Gigabit optical network.Traditional home network equipment mainly adopts single-beam single-polarized antenna design, which has become increasingly unable to meet the needs of high-quality network products under the background of large attenuation and strong interference.Antenna, as an indispensable component to realize conduction energy and air-interface electromagnetic wave transformation, can realize multiple functions by using its design freedom.High gain can reduce the power consumption of the radio frequency (RF) side to achieve the purpose of energy saving, and multi-beam can maintain high-performance network coverage without dead ends.Therefore, designing a multi-beam antenna with small size, high gain and flexible usage is of great value.Following the practical engineering and current academic research, a multi-beam antenna based on spoof surface plasmon polariton (SSPP) technology, covering the 5.1～5.9 GHz frequency band of Wi-Fi, was designed for home network products.Compared with traditional antennas, the test results of the antenna based on SPSS technology show that the coverage performance of the network in weak signal scenarios such as through-wall and cross-layer scenarios is improved greatly.It has great application prospects in increasingly miniaturized home terminal products.